Important clinical studies that changed the clinical practice of advanced breast cancer in 2024 - WU Song, YUAN Yang, JIANG Zefei (Zhongguo aizheng zazhi)
With advancements in molecular biology research and precision medicine, treatment options for advanced breast cancer have become increasingly diverse. In 2024, significant research progress has been achieved across different molecular subtypes of advanced breast cancer. Endocrine therapy combined with cyclin-dependent kinase 4/6 (CDK4/6) inhibitors has become the standard first-line treatment for hormone receptor-positive advanced breast cancer. Fulvestrant combined with abemaciclib serves as a treatment option after failure in CDK4/6 inhibitors. For patients with mutations in the AKT pathway, fulvestrant combined with the AKT inhibitor capivasertib provides significant long-term survival benefits. Trastuzumab deruxtecan (T-DXd) has emerged as a novel treatment option for patients with HER2 ultra-low expression. For HER2-positive advanced breast cancer, taxanes combined with trastuzumab and pertuzumab or pyrotinib remain the standard first-line treatments for trastuzumab-sensitive patients. The DESTINY-Breast07 trial evaluated the feasibility of using T-DXd as a first-line treatment, showing that whether used as monotherapy or in combination with pertuzumab, progression-free survival (PFS) was non-inferior to standard regimens reported in previous studies. For HER2-positive patients with brain metastases, updated results from the PERMEATE trial indicated that the combination of pyrotinib and capecitabine could provide overall survival benefits. The DESTINY-Breast12 trial demonstrated that T-DXd had similar antitumor activity against systemic and intracranial lesions, making it an effective treatment option for HER2-positive patients with brain metastases. Treatment strategies for advanced triple-negative breast cancer (TNBC) are shifting from conventional chemotherapy to regimens centered on chemotherapy combined with immunotherapy and antibody-drug conjugates (ADCs). The TORCHLIGHT trial showed that chemotherapy combined with the immune checkpoint inhibitor toripalimab improved the prognosis of patients with advanced TNBC. The NCC2167 trial found that when chemotherapy was combined with immunotherapy, metronomic chemotherapy offered superior efficacy and lower toxicity compared to conventional approaches. This article reviewed the significant research progress in advanced breast cancer in 2024. By summarizing related research data, it provides insights into the clinical experience of managing and making treatment decisions for patients with advanced breast cancer, serving as a reference for peers. Looking ahead, future clinical research should focus on individual differences among patients, tumor heterogeneity, and treatment resistance, aiming to improve treatment outcomes and the quality of life for patients with advanced breast cancer.